Reconstitution of novel mitochondrial uncoupling proteins UCP2 and UCP3 - Záckova, Markéta; Jezek, Petr (Bioscience reports, 2002)
Reconstitution of novel mitochondrial uncoupling proteins, human UCP2 and UCP3, expressed in yeast, was performed to characterize fatty acid (FA)-induced H+ efflux in the resulted proteoliposomes. We now demonstrate for the first time that representatives of physiologically abundant long chain FAs, saturated or unsaturated, activate H+ translocation in UCP2- and UCP3-proteoliposomes. Efficiency of lauric, palmitic or linoleic acid was roughly the same, but oleic acid induced faster H+ uniport. We have confirmed that ATP and GTP inhibit such FA-induced H+ uniport mediated by UCP2 and UCP3. Coenzyme Q10 did not further significantly activate the observed H+ efflux. In conclusion, careful instant reconstitution yields intact functional recombinant proteins, UCP2 and UCP3, the activity of which is comparable with UCP1.
Keywords: Mitochondria; membránové transportní proteiny; Yeasts; uncoupling protein 3; Humans; proteiny; iontové kanály; Proteins; Uncoupling Protein 3; Uncoupling Protein 2; lidé; mitochondrie; Membrane Transport Proteins; Mitochondrial Proteins; mitochondriální proteiny; kvasinky; transportní proteiny; Carrier Proteins; mastné kyseliny; uncoupling protein 2; Ion Channels; Fatty Acids